Implementation of PAI Learning Policies During A Pandemic: Opportunities and Challenges - Afiq Budiawan; A Rafiq Zainul Mun'im (Lembaga Anotero Scientific Pekanbaru, 2022)
This literature review aims to describe a literature review on PAI learning policies during the pandemic. The research method used is qualitative with a literature review approach. The stages of the research were carried out starting from article collection, article reduction, article display, discussion, and drawing conclusions. The data sources used are national and international journal articles in the last 5 years (2015-2020). The search results of the literature review show that there are positive learning style changes where students become more active and creative, there are also negative changes where there is a decrease in student learning motivation. In addition, technology also needs to continue to improve its quality as the most important means to support this process. It is hoped that the government will not turn a blind eye to problems that occur related to technology as a means of supporting online learning or distance learning